Dilema Media Massa di Era Digital: Antara Perlindungan Data Pribadi dan Kebebasan Pers Dalam UU PDP - Alamsyah, Rizki; Wiraguna, Sidi Ahyar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In an increasingly connected digital era, personal data has become a strategic asset that is vulnerable to misuse. The mass media, as an important part of the digital ecosystem, plays a dual role as a manager and disseminator of information involving individual data. The enactment of Law No. 27 of 2022 concerning Personal Data Protection (UU PDP) is an important milestone in the Indonesian legal system, but its implementation raises complex problems in mass communication practices. The main legal issue in this article lies in the tension between the media's obligation to protect personal data and press freedom in conveying information to the public. This study aims to examine the legal impact of the PDP Law on the mass media by examining the challenges, implications, and needs for regulatory adjustments. The approach used is the normative legal method, with a qualitative analysis of national laws and regulations (UU PDP, UU ITE, UU Press), GDPR as an international standard, and related legal literature. The results of the study indicate that the PDP Law demands significant reforms in data governance by media institutions, including transparency, security, data subject consent, and protection of sensitive data. On the other hand, the disorder of norms and the absence of an independent supervisory authority create gaps in implementation. This study also offers strategic recommendations for mass media to adjust journalistic practices and digital business with the PDP Law, including harmonization of journalistic codes of ethics and the use of data anonymization technology. In conclusion, the success of the PDP Law in the media sector requires synchronization of regulations, strengthening institutions, and increasing media actors' awareness of the principles of digital privacy rights.